The psychological clang of terrorism fear and stress on employees’ well-being - Shah, Syed Asad Ali; Alyaemni, Asmaa; Ali, Liaqat (Frontiers in Psychology, 2025)
The education sector is a conspicuous target for terrorist attacks, significantly impacting the quality of life and well-being of its employees. Job satisfaction is a key indicator of employee well-being; thus, understanding the link between the fear of terror and job satisfaction is essential but remains unexplored. This study examines the association through the lens of terrorism-induced stress in the education sector of the two most terrorism-affected regions in Pakistan. Data were collected using a structural questionnaire and were analyzed through structural equation modeling techniques. This research study explored a significant relationship between the fear of terrorism and job satisfaction, which is partially mediated by terrorism-induced stress. Implications for improving a healthy work environment in terrorism-affected regions and recommendations for future studies based on the findings are discussed.